Desunión conyugal como factor determinante de la depresión infantil en un niño de 9 años de edad - Lavayen Pincay, Ninoska Victoria (2019)
Children who have their parents separated have difficulties in their behavior, emotional status such as performing daily life activities either in school or in interpersonal relationships as opposed to children who have their parents together in marriage or in fact, the problem of marital disunity contributes to the child the development of a state of discouragement where this situation affects in such a way that it feels discouraged, the purpose of this research work is the collection of data to analyze how this rupture has a determining factor in childhood depression. This research was carried out based on the case study methodology in which information is gathered through different techniques such as semi-structured interviews, medical history, tests that were applied and of paramount importance for obtaining more where they gave their validity. All this was intended to make conclusions and recommendations intended to help the infant and improve the quality of life he is going through, so that the best decision can be used to improve the development of the Less